2017
DOI: 10.1158/1078-0432.ccr-16-2026
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the Immune Cell Composition in Premalignant Breast Tissue that Precede Breast Cancer Development

Abstract: Little is known about the role of the immune system in the earliest stages of breast carcinogenesis. We studied quantitative differences in immune cell types between breast tissues from normal donors and those from women with benign breast disease (BBD). A breast tissue matched case-control study was created from donors to the Susan G. Komen for the Cure Tissue Bank (KTB) and from women diagnosed with BBD at Mayo Clinic (Rochester, MN) who either subsequently developed cancer (BBD cases) or remained cancer-fre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 40 publications
3
49
0
Order By: Relevance
“…These data suggest that CLS-B-associated adipose tissue inflammation occurs in a significant subset of individuals with BBD. We have previously reported that lobules of BBD tissues have a significantly higher density of CD68-positive macrophages, among other immune cell types, compared with that of lobules in KTB donor breast tissues (24). Together, these findings support the hypothesis that BBD is associated with an epithelial and stromal chronic inflammatory environment.…”
Section: Discussionsupporting
confidence: 76%
“…These data suggest that CLS-B-associated adipose tissue inflammation occurs in a significant subset of individuals with BBD. We have previously reported that lobules of BBD tissues have a significantly higher density of CD68-positive macrophages, among other immune cell types, compared with that of lobules in KTB donor breast tissues (24). Together, these findings support the hypothesis that BBD is associated with an epithelial and stromal chronic inflammatory environment.…”
Section: Discussionsupporting
confidence: 76%
“…In benign breast disease tissues, we observe decreasing CD8+/CD103+ cells with increasing epithelial proliferation. This is particularly interesting given that our previous study showed higher densities of other immune cell types in lobules of BBD compared to normal tissues, suggesting greater inflammation in these tissues [8]. Activation of NFkb, a hallmark of inflammation, is a major factor in downregulation of E-cadherin in epithelial cells [16].…”
Section: Discussionmentioning
confidence: 86%
“…In most of these studies, the CD103expressing T cells were predominantly intraepithelial and CD103+ cells were more strongly associated with outcomes than CD8+ T cells. We recently reported on immune cells in normal and premalignant breast tissues, with a finding of CD8+ T cells in close association with breast epithelium, representing the main characteristic of mucosal IELs [8]. Therefore, we hypothesized that breast epithelium also harbors similar cytotoxic T cells that may play a role in antitumor immunity.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…The underlying mechanism may be that B cells promote T‐cell antitumor immune responses by acting as APCs. Likewise, the conclusion has been confirmed in melanoma, breast cancer and colorectal cancer . These results are also consistent with a previous study, which demonstrated that B cells were required for optimal induction of CD4 + and CD8 + T cells in controlling tumor invasion and metastasis .…”
Section: Dual Aspects Of the Biological Function Of B Cellsmentioning
confidence: 99%